Baseline Assessment of the Vegetable Gardens (Gulayan Sa Paaralan) in Public Elementary and Secondary Schools - Molijon, Anita; De La Rama, Juana (JPAIR Institutional Research, 2014)
“Gulayan sa Paaralan” (Vegetable Gardens) is one of the strategies of the National Greening Program of the government implemented to help promote food security. This study was undertaken to determine its status five years after its implementation. Descriptive research design was used. The 242 samples were randomly selected from the list of schools implementing Gulayan sa Paaralan from the Department of Agriculture-Regional Field Unit in Region X. A survey was done in 16 elementary and six high schools of Cagayan de Oro City, Philippines. About 77% of the schools maintained vegetable gardens to serve as food basket or main source of vegetables to sustain supplementary feeding. Also, 77% of the schools surveyed used organic vegetable production. The schools taught agriculture in their Edukasyong Pantahanan at Pangkabuhayan (EPP) in the elementary schools and also in the Technology Livelihood Education (TLE) classes in the high schools. About 87% of the 220 pupils and students interviewed said that Gulayan sa Paaralan through vegetable gardening helped the school and their families economically. It is concluded that schools are still vibrant in theimplementation of the program. Through the program, the pupils learned to love and appreciate the field of agriculture.
Keywords: Educational Planning and Management; Gulayan sa Paaralan; organic production; vegetable gardening; love of agriculture; descriptive design; Cagayan de Oro City; Philippines